Comparative histomorphological study of non affected and affected liver by fascioliasis in Black Bengal goat (Asian Journal of Medical and Biological Research, 2016)
The purpose of this study was to comparative histomorphological investigation of the non affected and affected liver by fascioliasis in Black Bengal goat. The average weight of affected livers was 511.20±14.10 gm which was significantly (p